Vitamin D and Physical Performance in Elderly Subjects: The Pro.V.A Study - Toffanello, Elena D.; Perissinotto, Egle; Sergi, Giuseppe; Zambon, Sabina; Musacchio, Estella; Maggi, Stefania; Coin, Alessandra; Sartori, Leonardo; Corti, Maria-Chiara; Baggio, Giovannella; Crepaldi, Gaetano; Manzato, Enzo (PLOS ONE, 2012)
Background The role of Vitamin D in musculoskeletal functionality among elderly people is still controversial. We investigated the association between serum 25-hydroxyvitamin D (25OHD) levels and physical performance in older adults. Methods 2694 community-dwelling elderly women and men from the Progetto Veneto Anziani (Pro.V.A.) were included. Physical performances were assessed by: tandem test, 5 timed chair stands (TCS), gait speed, 6-minute walking (6 mW) distance, handgrip strength, and quadriceps strength. For each test, separate general linear models and loess plots were obtained in both genders, in relation to serum 25OHD concentrations, controlling for several potential confounders. Results Linear associations with 25OHD levels were observed for TCS, gait speed, 6 mW test and handgrip strength, but not for tandem test and quadriceps strength. After adjusting for potential confounders, linear associations with 25OHD levels were still evident for the 6 mW distance in both genders (p = .0002 in women; <.0001 in men), for TCS in women (p = .004) and for gait speed (p = .0006) and handgrip strength (p = .03) in men. In loess analyses, performance in TCS in women, in gait speed and handgrip strength in men and in 6 mW in both genders, improved with increasing levels of 25OHD, with most of the improvements occurring for 25OHD levels from 20 to 100 nmol/L. Conclusion lower 25OHD levels are associated with a worse coordination and weaker strength (TCS) in women, a slower walking time and a lower upper limb strength in men, and a weaker aerobic capacity (6 mW) in both genders. For optimal physical performances, 25OHD concentrations of 100 nmol/L appear to be more advantageous in elderly men and women, and Vitamin D supplementation should be encouraged to maintain their 25OHD levels as high as this threshold.